SEMIOTICS IN GOVERNORS DEBATING (SYSTEMIC FUNCTIONAL LINGUISTICS STUDY) - Akmal Akmal; Zulkarnain Sirait (Smart Education, 2023)
Abstract: The research aims to identify the semiotics aspects in the Candidates Of North Sumatera Governor 2013 2018. The communications in the data convey peoples emotions, feelings, and messages through expressive actions. By analyzing the communication, the people are able to be easy to understand the communication by using the body moving in semiotics in daily communication and ease people to understand messages delivered primarily in front of the public and help the speakers deliver ideas or opinions to the audiences. The research was conducted through qualitative descriptive analysis. The research data was the public debate on TV One Channel of The Candidates Of North Sumatera Governor 2013 2018, and the source of data was www.youtube.com. The research data were five candidates of the governors in the general election 2013 in 240 minutes. Body movement expression can be found in all five candidates speeches with the highest number of gestures performed by Chairman Harahap. The research results were that Chairman Harahap has 21 gestures, Effendi Simbolon has 18 gestures, Gus Irawan Pasaribu has 16 gestures, Gatot Pujo Nugroho has 12 Amri Tambunan has only the body movement (semiotics).Keywords: semiotics; body movement; debating Abstrak: Penelitian ini bertujuan untuk mengidentifikasi aspek semiotika pada Calon Gubernur Sumatera Utara 2013 2018. Komunikasi dalam data tersebut menyampaikan emosi, perasaan, dan pesan masyarakat melalui tindakan ekspresif. Dengan menganalisis komunikasi, masyarakat dapat dengan mudah memahami komunikasi dengan menggunakan gerak tubuh secara semiotika dalam komunikasi sehari-hari dan memudahkan masyarakat untuk memahami pesan yang disampaikan terutama di depan umum dan membantu pembicara menyampaikan ide atau pendapat kepada audiens. Penelitian dilakukan melalui analisis deskriptif kualitatif . Data penelitian ini adalah debat publik di Channel TV One Calon Gubernur Sumut 2013 2018, dan sumber datanya adalah www.youtube.com. Data penelitian adalah lima calon gubernur pada pemilihan umum tahun 2013 dalam waktu 240 menit. Ekspresi gerakan tubuh, dapat ditemukan pada kelima pidato kandidat dengan jumlah gestur terbanyak dilakukan oleh Ketua Harahap. Hasil penelitian adalah Ketua Harahap memiliki 21 gestur, Effendi Simbolon memiliki 18 gestur, Gus Irawan Pasaribu memiliki 16 gestur, Gatot Pujo Nugroho memiliki 12 Amri Tambunan hanya memiliki gerak tubuh (semiotika).